SAT-102 Self-efficacy As A Predictor Of Weight Loss In Veterans With Obesity Participating In Medical Weight Management. - Parziale, Andrew (J Endocr Soc, 2019)
Background: Overweight and obesity are major health burdens in veterans, occurring at higher rates than the general population (78% vs 69%) and associate with chronic disease development. Self-efficacy is a person's ability to overcome the difficulties inherent in performing a specific task in a particular situation such as smoking cessation. We evaluated if a simple self-efficacy score may serve as a predictor of weight control in de-identified records of veterans with obesity undergoing a weight loss intervention consisting of lifestyle modification with pharmacotherapy through a VA weight management clinic. Methods We reviewed deidentified records for 22 obese (BMI ≥ 30) participants (17 males, 5 females, age range = 43–69, race/ethnicity 45% Black, 32% White, 18% Latino, and 5% Asian) in the VA weight management clinic. As part of the intake assessment, we used 2 validated questions to assess participants’ confidence in their ability to lose weight. Individuals were asked: “How ready are you to commit time, energy and resources to weight loss therapy?" and "How confident are you in your ability to lose weight?" Answers were rated from 1 (not ready or not confident) to 3 (ready or confident). Self-efficacy was scored as high (5-6), intermediate (3-4) or low (0-2). Results: Participants were on average 56 years old with weight of 275±49 lb at baseline. Eight records were classified as having high self-efficacy, 7 had moderate self-efficacy, and 3 had low self-efficacy. After 3 months of lifestyle plus pharmacotherapy intervention, weight loss in the high self-efficacy group was 8.8 ± 4.6 lb vs -0.4 ± 1.2 lb (mean±SE, p = 0.088) in the non-high self-efficacy group. Excess body weight in high vs non-high self-efficacy groups at 3 months was 3.08% ± 0.02% vs -0.26% ± 0.01 (p = 0.094). Conclusions: Our data suggests that veterans with obesity and high self-efficacy may lose more weight than those with lower self-efficacy. This simple tool may serve as an important first screen for weight management clinical practice. References -Diabetes Prevention Program Research, G., et al., 10-year follow-up of diabetes incidence and weight loss in the Diabetes Prevention Program Outcomes Study. Lancet, 2009. 374(9702): p. 1677-86. -Tsai et al. Readiness Redefined: A Behavioral Task during Screening Predicted 1-Year Weight Loss in the Look AHEAD Study. Obesity (Silver Spring). 2014 April ; 22(4): 1016–1023. doi:10.1002/oby.20648.